Interaction and online courses for satisfactory university learning during the COVID-19 pandemic - Kang, Dongsuk; Park, Min Jae (International Journal of Management Education, 2022)
The global COVID-19 pandemic that commenced in 2019 and the resulting prolonged social distancing have converted numerous universities' offline courses to online ones. In South Korea, which is facing a low birth rate and a decrease in school-age population, university students of Generation Z have actioned lawsuits to pursue tuition refunds and have raised the issue of the low quality of university courses through social media. This research establishes research problems of the relationship between student satisfaction with online courses and influencing factors and the relationship between their satisfaction and continual use of the course system. This research obtained a sample of 123 undergraduate students majoring in management. This study implemented questionnaire with the sample and utilized the analysis of generalized structural equation modelling (GSEM). The study found that students' feelings about instructors' useful interaction (feedback) with them and their preference for online courses positively affected their satisfaction with those courses. Satisfaction also exerted a positive effect on their course recommendation to others. The implications of this finding are that instructors and universities need to enhance course quality and the students’ satisfaction level with online courses in a highly competitive where private educational services (e.g., massive open online courses [MOOC], Youtube) are offered and the number of new students is decreasing.
Keywords: Class interaction; Course quality; Course satisfaction; GSEM; Online education; University innovation